More Than Schooling : Understanding Gender Differences in the Labor Market When Measures of Skill Are Available - Gunewardena, Dileni (World Bank, Washington, DC, 2018)
This paper uses measures of cognitive and noncognitive skills in an expanded definition of human capital to examine how schooling and skills differ between men and women and how those differences relate to gender gaps in earnings across nine middle-income countries. The analysis finds that post-secondary schooling and cognitive skills are more important for women's earnings at the lower end and middle of the earnings distribution, and that men and women have positive returns to openness to new experiences and risk-taking behavior and negative returns to hostile attribution bias. Especially at the lower end of the earnings distribution, women are disadvantaged not so much by having lower human capital than men, but by institutional factors such as wage structures that reward women's human capital systematically less than men's.